Effectiveness of carbon dioxide emission target is linked to country ambition and education level - Yuheng Zheng; Rui Shan; Wangtu (Ato) Xu; Yueming (Lucy) Qiu (Communications Earth & Environment, 2024)
Abstract In response to the Paris Agreement, a growing number of countries, 123 in total, have committed to carbon reduction targets. While existing research has assessed various policies’ effectiveness in achieving these targets, the potential of the act of goal-setting itself as a policy instrument has been underexplored. Here we leveraged a comprehensive panel dataset spanning 163 countries from 2011 to 2022 and employed a rigorous difference-in-difference model. Empirical findings reveal that both proposing carbon reduction targets and setting higher targets effectively reduce emissions intensity. The mechanism driving the impact of carbon reduction targets on CO2 emissions centers on the level of education, rather than renewable energy capacity, requiring further investigation to the mechanism. Subsequent analysis establishes connections between target levels and renewable energy capacity. Our results advocate for dynamic updates of carbon reduction targets aligned with renewable energy capacity when formulating climate objectives.